The Effect of Oligopin Supplementation on Hormonal and Metabolic Profiles in the Polycystic Ovary Syndrome: A Randomized Controlled Trial - Qorbani, Mostafa; Sanginabadi, Milad; Mohajeri-Tehrani, Mohammad Reza; Karimi, Sara; Gerami, Hadis; Mahdavi-Gorabi, Armita; Shirzad, Nooshin; Samadi, Majid; Baygi, Fereshteh; Hosseini, Saeed; Mansour, Asieh (Frontiers in Endocrinology, 2020)
Background: A double blind clinical trial was performed to evaluate whether the polycystic ovary syndrome (PCOS)-specific serum markers and metabolic parameters would change in the women with PCOS during the three-month administration of oligopin. Methods: In this double-blind multicenter trial, we randomly assigned 80 PCOS women, based on a 1:1 ratio, to receive oligopin (n= 40) or maltodextrin as placebo (n = 40) for up to 3 months. As PCOS-specific outcomes, we investigated the changes in testosterone, sex hormone binding globulin (SHBG), free androgen index (FAI), dehydroepiandrosterone (DHEA), follicle-stimulating hormone (FSH) and luteinizing hormone (LH). Secondary end points were metabolic (fasting glycaemia, hemoglobin A1c (HbA1c), lipids, insulin resistance (HOMA-IR)), anthropometrics parameters and blood pressure from the baseline to the end of treatment. We investigated serum transaminase, alkaline phosphatase (ALP), creatinine (Cr) and blood urea nitrogen (BUN) levels as hepatic and kidney outcomes, respectively. Results: The first participant was enrolled on April 18, 2018, and the last study visit took place on May 14, 2019. PCOS-specific serum parameters did not change during the three-month administration of oligpin (p > 0.05), except for a small increase in the FSH levels (p=0.03). Oligopin neither changed the metabolic profile nor the anthropometric parameters or blood pressure. ALP levels was significantly increased in placebo group, as compared with oligopin (p=0.01). Conclusion: Oligopin supplementation does not seem to be exerting a beneficial effect on both hormonal and metabolic parameters in the women with PCOS.